Identification and functional analysis of a novel CSNK2A1 frameshift variant in stillbirth - Zhang, Nannan; Han, Miao; Zhao, Tong; Tang, Xinxin; Wang, Zhiwei; Du, Yunqiu; Wang, Leilei (Frontiers in Genetics, 2025)
BackgroundCasein Kinase II Subunit Alpha (CK2α), the catalytic subunit of protein kinase CK2, is encoded by CSNK2A1. This kinase catalyzes substrate phosphorylation and regulates diverse cellular processes including cell cycle progression, apoptosis, and transcription. CSNK2A1 is associated with Okur-Chung Neurodevelopmental Syndrome (OCNS, OMIM: 617062). Although CSNK2A1 functional deficiency is implicated in impaired embryonic development, prenatal case reports remain scarce.MethodsClinical data and fetal umbilical cord blood samples were collected. Whole-genome sequence (WGS) was used for potential pathogenic variants identification, followed by Sanger sequencing to validate the variant. Bioinformatic tools were employed to predict the 3D structure of the variant. Wild-type and mutant CSNK2A1 overexpression plasmids were constructed to investigate the functional consequences of the variant.ResultA 33-year-old pregnant woman without adverse obstetric history. At 34+4 weeks, ultrasound showed an intracranial abnormal echoes, multiple cardiovascular anomalies, and stillbirth had occurred at 35 weeks. WGS identified a novel frameshift mutation c.1020_1021delAG (p.Gly342Glnfs*57) in the CSNK2A1 gene. Bioinformatics analysis indicated structural modification in mutant proteins. In vitro kinase assays showed that the variant did not impair kinase activity. Quantitative analysis demonstrated significantly elevated mutant mRNA levels but reduced protein expression compared to wild-type. Elevated ubiquitination in mutants potentially explains diminished CSNK2A1 protein abundance.ConclusionWe report a novel CSNK2A1 frameshift mutation that significantly reduces protein expression and impairs gene function. These findings expand our understanding of CSNK2A1’s genetic diversity and underscore the importance of comprehensive functional analyses to achieve accurate diagnosis. This study facilitates prenatal diagnosis of CSNK2A1-related disorders and informs clinical decision-making for carriers.